1997
DOI: 10.1016/s1353-2561(98)00023-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of oil spill remote sensing

Abstract: The technical aspects of oil spill remote sensing are examined and the practical uses and drawbacks of each technology are given with a focus on unfolding technology. The use of visible techniques is ubiquitous, but limited to certain observational conditions and simple applications. Infrared cameras offer some potential as oil spill sensors but have several limitations. Both techniques, although limited in capability, are widely used because of their increasing economy. The laser fluorosensor uniquely detects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(129 citation statements)
references
References 17 publications
2
126
0
1
Order By: Relevance
“…Thus, the calming effect of oil can be confused with low-wind areas. In addition, other naturally occurring phenomena, including biogenic surfactants, can cause dark areas in SAR imagery and produce false positives (i.e., areas that look like oil but are not) [Fingas and Brown, 1997;Nunziata et al, 2009].…”
Section: Polarimetric Sar Observationmentioning
confidence: 99%
“…Thus, the calming effect of oil can be confused with low-wind areas. In addition, other naturally occurring phenomena, including biogenic surfactants, can cause dark areas in SAR imagery and produce false positives (i.e., areas that look like oil but are not) [Fingas and Brown, 1997;Nunziata et al, 2009].…”
Section: Polarimetric Sar Observationmentioning
confidence: 99%
“…The Landsat technology was the first remote sensing method adopted in the analysis of hydrocarbons however, with improvements in technology, the microwave technology became a more preferred remote sensing method. Active microwave sensors like Synthetic Aperture Radars (SAR) capture two-dimensional images of oils [18][19]. Prior studies reveal that ultraviolet (UV) ranges of the spectrum have shown a wider geological application [20][21][22], although its major challenge lies in the intense absorption of UV radiation by the atmosphere i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing need for monitoring large oil spills, estimating the location and extent of the spill (Fingas & Brown, 1997;Fingas & Brown, 2014). Remote sensing is an important part of oil spill response, as oil spills can be monitored on the open sea or ocean on a 24h basis (Fingas & Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%